TECHNOLOGICAL LEADERSHIP AND ICT LITERACY AS KEYS TO INCREASING INNOVATIVE TEACHER BEHAVIOR - Dasmo, Dasmo; Notosudjono, Didik; Wati, Septa (Universitas Labuhanbatu, 2025)
Purpose-Technological leadership and ICT literacy are important factors in improving teachers' innovative behavior. This study is essential, considering the rapid development of information technology that requires teachers to innovate. This study aims to analyze the direct influence of technological leadership and ICT literacy on innovative teacher behavior, the direct influence of technological leadership on ICT literacy, and the indirect influence of technological leadership on innovative behavior through ICT literacy.Methodology-This study uses path analysis. The sample of this study was 136 private high school teachers in Depok City, West Java, obtained through multistage random sampling techniques.Findings-Technological leadership positively and significantly influences teachers' innovative behavior with a p-value of 0.000 (<0.05). ICT literacy also positively and significantly influences teachers' innovative behavior, with a p-value of 0.001 (<0.05). Technology leadership has a positive and significant direct effect on ICT literacy, with a p-value of 0.000 (<0.05). The indirect impact of technology leadership on teacher innovative behavior through ICT literacy is insignificant, with a p-value of 0.857 (>0.05). ICT literacy has not played a significant role as a mediator, where the direct effect is stronger than the indirect effect.Significance- The strategy that can be used to improve teacher innovative behavior is to strengthen technology leadership and ICT literacy. Improving technology leadership can be achieved by improving technology infrastructure and fostering professional excellence for principals. Meanwhile, ICT literacy can be strengthened by providing teachers with skills to create, manage, access, and disseminate information, contribute to public knowledge, and understand the legal aspects of ICT.Keywords: Technological leadership, ICT literacy, Innovative teacher behavior